Optimal configuration of cooperative stationary and mobile energy storage considering ambient temperature: A case for Winter Olympic Game. (1st November 2022) - Meng, He; Jia, Hongjie; Xu, Tao; Wei, Wei; Wu, Yuhan; Liang, Lemeng; Cai, Shuqi; Liu, Zuozheng; Wang, Rujing; Li, Mengchao
Highlights: A thermal management model of CESS is developed considering the ambient temperature. A refined LCC model is proposed to accurately track the BESS performance. A collaborative operation scheme of SESSs and VSCs in AC/DC hybrid system is presented. A coordinated operation strategy of SESS and MESS is proposed under various scenarios. A two-stage capacity allocation model of SESS and MESS in AC/DC system is established. Abstract: The international mega-event, such as the Winter Olympic Game, has been considered as one of the most carbon intensive activities worldwide. The commitment of fully renewable energy accommodation and utilization while ensuring the extreme high reliability has brought significant challenges on system operation due to the stochastic nature of the renewables. The battery energy storage system (BESS) composed of stationary energy storage system (SESS) and shared mobile energy storage system (MESS) can be utilized to meet the requirements of short-term load surges, renewable accommodation and emergency power supply for important loads during the mega-event. The BESS can continue to serve the venues' electricity consumption to satisfy the carbon neutrality after the event. On the other hand, the low ambient temperature of Winter Olympic game has significant impact on BESS's degradation and performance which need to be integrated to the charging and discharging models of BESS. To this end, a joint two-stage optimal configuration method considering the ambient temperature of SESS and MESS has been developed to support the mega-event carbon reduction, to reduce redundant BESS capacity allocation and improve the system life cycle cost-benefit. Simulation results have demonstrated the rationality and effectiveness of the collaborative operation of SESS and MESS under various scenarios.